Analisis Fungsional Terhadap Kebijakan Pemerintahan Pu Sindok Pada Abad Ke-10 M - Hari Fitria Utama; Arif Subekti (Badan Riset dan Inovasi Nasional (BRIN), 2023)
Many inscriptions from Pu Sindok's reign (929–948) can be discovered across eastern Java. The researchers have found 23 inscriptions with year dates that detail the laws that were in effect under Pu Sindok's rule. Policies are written in the inscriptions as sima makudur and sima punpunan. Because there are so many sources in these inscriptions, it is possible to recreate historical events under Pu Sindok's reign and assess his implemented policies. This article uses Robert K. Merton's functional analysis to examine Pu Sindok's policies. The outcomes of this article's descriptive qualitative research techniques and astabrata parameters are the manifest, latent, and dysfunctional functions of Pu Sindok's policies. Keywords: Pu Sindok; functional analysis; policies